2008
DOI: 10.1080/13625180701617621
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about sexual and reproductive health of adolescents in Europe?

Abstract: While the SRH of most European adolescents is good, they remain a vulnerable population. Lack of standardized reproductive indicators and age specific aggregate data make it difficult to accurately assess the situation in individual countries or perform cross country comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 16 publications
6
50
1
4
Order By: Relevance
“…More than 20% of adolescents aged 15-19 years have ever been pregnant in 20 of the 26 countries surveyed as part of the Demographic Health Surveys (DHS) in sub-Saharan Africa and South/Southeast Asia [42 ]. European data show that over the past 20 years unplanned adolescent pregnancies have declined except for in the UK, where the rate has been stable [43]. Similarly to the developing countries, factors associated with teen pregnancy in the European Union included lower socioeconomic status, leaving school early or disliking school, family disruption, early sexual initiation, and increasing number of partners [44].…”
Section: Teen Pregnancymentioning
confidence: 98%
“…More than 20% of adolescents aged 15-19 years have ever been pregnant in 20 of the 26 countries surveyed as part of the Demographic Health Surveys (DHS) in sub-Saharan Africa and South/Southeast Asia [42 ]. European data show that over the past 20 years unplanned adolescent pregnancies have declined except for in the UK, where the rate has been stable [43]. Similarly to the developing countries, factors associated with teen pregnancy in the European Union included lower socioeconomic status, leaving school early or disliking school, family disruption, early sexual initiation, and increasing number of partners [44].…”
Section: Teen Pregnancymentioning
confidence: 98%
“…Studies of sexual behaviour in the UK have been led by a concern to reduce teenage pregnancy (Phoenix 1993), propelled in part by the fact that the UK has one of the highest rates of teenage pregnancy in Europe (Avery and Lazdane 2008;UNICEF 2001;United Nations Statistics Division 2010). Lack of research is most likely related to the 'unproblematic' sexual behaviour reported by British Asians -an analysis of data collected through the most recent British National Survey of Sexual Attitudes and Lifestyles in 2000 showed that Indian (and Pakistani) men and women reported fewer sexual partnerships, later first intercourse and a lower prevalence of STIs than other ethnic groups .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays adolescents' contraceptive behaviour is an issue of general Public Health concern, since adolescents continue to be a population at risk for both sexual and reproductive health 1 . In particular, the rate of unintended pregnancy in Western Europe is still high and it is estimated that in 2008 around 30% of all pregnancies in Europe ended in induced abortion 2 .…”
Section: Introductionmentioning
confidence: 99%